(3HOjYjI YHO GdQMef Hf eMeO Hf jhSa GdYdhis - (3YHO GdQMef Hf eMeO Hf jhSa GdYdhj,J (B803 (3g` s ((3YeQ CfSi Hf eMeO OjH GdUbYGf GdHjQhJi s)
(3ChdgG (B:s
(3Sd eG HSdeG hSd eG QH GdSde hNU WjHI eChi GdWjH hGdcQe s
(3BNQgG (B:s
(3hGddBd hGdUMH eG ZfJ eWhbI YO GdfLhe hdeM GdWQa ai GdXde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B194s
Keywords: (3GdHdGZIs